2018
DOI: 10.5232/ricyde2018.05205
|View full text |Cite
|
Sign up to set email alerts
|

Orientaciones de meta como mediadoras en la relación entre perfeccionismo y ansiedad precompetitiva. [Goal orientations as mediators in the relationship between perfectionism and precompetitive anxiety].

Abstract: Orientaciones de meta como mediadoras en la relación entre perfeccionismo y ansiedad precompetitiva Goal orientations as mediators in the relationship between perfectionism and precompetitive anxietyHeriberto Antonio Pineda-Espejel, Edgar Alarcón, Zaida López-Ruiz y Marina Trejo Universidad Autónoma de Baja California, Facultad de Deportes. MexicoEl objetivo de este estudio fue analizar el efecto del perfeccionismo estado y las orientaciones de meta, sobre la ansiedad precompetitiva, a través de dos modelos qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
1
0
1
Order By: Relevance
“…These findings are also consistent with those of previous studies that report differences between boys and girls in non-competitive, nonsports samples [21,22,64]. Moreover, and in line with previous scientific findings [35,52,59], as competitiveness in their achievement trajectories intensifies, aggressive tendencies also increase, but prosocial tendencies decrease in both boys and girls. However, studies based on the perfectionism social disconnection model [20,21,33] point out that girls who exhibit self-oriented perfectionism tend towards higher levels of agreeableness and gregariousness [33,42].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are also consistent with those of previous studies that report differences between boys and girls in non-competitive, nonsports samples [21,22,64]. Moreover, and in line with previous scientific findings [35,52,59], as competitiveness in their achievement trajectories intensifies, aggressive tendencies also increase, but prosocial tendencies decrease in both boys and girls. However, studies based on the perfectionism social disconnection model [20,21,33] point out that girls who exhibit self-oriented perfectionism tend towards higher levels of agreeableness and gregariousness [33,42].…”
Section: Discussionsupporting
confidence: 93%
“…Prior research shows that behaving prosocially is significantly related to achievement tendencies [52,56,59]. It is also worth noting that other studies have shown that adaptive perfectionism is mediated by the practice of physical activity and adolescents' goals in federated sports [60], where sport intensity and social goals serve as personal standards for the good psychosocial development of the adolescent [61].…”
Section: Discussionmentioning
confidence: 95%
“…Con respecto a la ansiedad competitiva se comparte con los autores Pineda, Alarcón, López y Trejo (2018). Cuando consideran que es un tipo de ansiedad de estado, que refiere a la reacción emocional de aprehensión, tensión y nerviosismo ante situaciones de competencia, la cual puede favorecer o perjudicar el rendimiento de los deportistas.…”
Section: Introductionunclassified